Evaluating the Rutting Resistance of Asphalt Mixtures Containing Waste Steel and Treated Recycled Concrete Aggregate - Hussein, Ghufran Abd Al-Mohsen; Ismael, Mohammed Qadir (Civil Engineering Journal, 2024)
Using treated recycled concrete aggregate (RCA) in asphalt with waste steel reinforcement benefits the economy and the environment while delaying asphalt pavement deterioration. This study examined the impact of using RCA in several percentages reinforced by three dosages of waste steel: 0.3, 0.6, and 0.9 added as a proportion of mixture weight. The RCA was immersed in a 0.1M Hydrochloric acid solution for one day to treat the weak cement mortar in RCA and reduce the thickness of this layer. The assessment was carried out in a laboratory using the typical Marshall test to determine the optimum quantity of asphalt contents, the volumetric properties of asphalt mixtures, and the wheel tracking test; the study involved ten rectangular slabs measuring 30×40×5 cm, and they were repeatedly subjected to 700 N wheel loads at 55°C to test their rut resistance. According to the study, while Marshall's stability increased, adding waste steel and RCA did not significantly alter the volumetric properties of asphalt mixes. The greatest improvement in Marshall stability, 45.18% over the conventional mix, was seen in the mix, including 75% RCA and 0.9% waste steel. The rutting performance decreased with the addition of RCA and rose with the inclusion of waste steel. The results indicate that adding waste steel to asphalt mixtures effectively increases the rutting resistance. The mixture with 50% RCA and 0.9% waste steel showed less rutting depth of 25.01% than the conventional mix. Doi: 10.28991/CEJ-2024-010-11-011 Full Text: PDF